Targeted delivery of agrochemical loaded gold nanoparticles in plant - Bay, Ronald Yon Kan (Nanyang Technological University, 2021)
The global population is estimated to be 9.7 billion by 2050 and food demand will drastically increase. In order to satisfy this, there are many agricultural research to improve the yield production. Nanotechnology in particular has brought many advances to the agriculture industry. There is various research on using NPs for various applications. In this paper, nanofertilizers will be the main focus where Beta-Cyclodextrin (ß-CD) capped Gold Nanoparticles (AuNPs) will be loaded with nutrients, namely Mg and Cu, required by the plant and applied through direct foliar feeding. EDTA-Mg, EDTA-Cu, CuAcetate and MgSO4 were the used to load into the ß-CD capped AuNPs. Observations of ß-CD capped AuNPs loaded with EDTA-Cu and EDTA-Mg showed slower growth compared to ß-CD capped AuNPs loaded with CuAcetate and MgSO4. However, ß-CD capped AuNPs loaded with EDTA-Cu and EDTA-Mg have a sudden spurt in growth nearing the end of the experiment. As EDTA forms stable complex with the metal ions, this could be reason that resulted in a slower release of metal ions, thus a slower growth in the beginning followed by a faster growth. Further experiments are to be conducted and explored to have a more accurate finding.